Copper-catalyzed intramolecular cross dehydrogenative coupling approach to coumestans from 2′-hydroxyl-3-arylcoumarins. Issue 30 (3rd June 2019) - Song, Xianheng; Luo, Xiang; Sheng, Jianfei; Li, Jianheng; Zhu, Zefeng; Du, Zhibo; Miao, Hui; Yan, Meng; Li, Mingkang; Zou, Yong
Abstract : A copper-catalyzed intramolecular cross dehydrogenative C–O coupling reaction of 2′-hydroxyl-3-arylcoumarins was developed. Abstract : A copper-catalyzed intramolecular cross dehydrogenative C–O coupling reaction of 2′-hydroxyl-3-arylcoumarins was developed. This protocol provided a facile and efficient strategy for the construction of natural coumestans and derivatives in moderate to high yields. This transformation exhibited good functional group compatibility and was amenable to substrates with free phenolic hydroxyl groups.